Development of air purifier operation guidelines using grey box models for the concentrations of particulate matter in elementary school classrooms. Issue 5 (4th May 2023) - Park, Sowoo; Song, Doosam; Jo, Young Min; Park, Ju-Hyeong; Lee, Tae Jeong; Koo, Junemo
Abstract: Considering the hazardous effects of particulate matter (PM) exposure on students and teachers and the high PM concentration issue in South Korea, air purifiers have recently been installed in most classrooms to improve air quality. However, some on-site challenges, such as operational costs and noise, have been issues with the continuous operation of air purifiers. Therefore, a guideline is needed to dynamically predict the indoor PM concentration based on the changes in outdoor PM concentration and activate the air purifiers only when necessary. This study develops a grey-box model that uses measured data and physical differential equations to perform the given objective and verifies its accuracy using ASTM D5157. Modeling and analysis results have obtained information that can form the basis for developing guidelines to address PM issues in schools: The air purifier should be operated during periods where the predicted values exceed the limit in closed windows and the air purifier is not operating. It was also confirmed that the need for the operation of the air purifier varies between schools and classrooms under the same outdoor PM concentration. Indoor PM concentration increased significantly after students' simultaneous mass movement, necessitating air purifiers' operation before and after the events. The pre-filter of the heater also aided in the removal of coarse PM. Additionally, the limitations and future development directions of the model were discussed. Copyright © 2023 American Association for Aerosol Research GRAPHICAL ABSTRACT: UF0001